The Impacts of Task-Based Activities on Learners’ Grammatical Acquisition and Motivation at Dong Nai Technology University - Thi Yen Nhi Ha; Hong Hai Pham; Trung Nghia Tran (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2023)
The study aims to measure the effect of Task-based language teaching on grammatical achievement and the motivation of EFL learners at Dong Nai Technology University. The research will conduct a quick grammar test to administer 48 students at the school to achieve this goal. After sitting the test, the learners will undergo a 6-week course applying task-based language teaching. Before the treatment, one certified instructor-made grammar test about the learning units will be encompassed as the pre-test. Furthermore, a motivation questionnaire will be carried out in this group at the research's beginning and end. Afterward, the learners will learn through the treatment, which is learning through the implementation of Task-based language teaching. After six weeks of treatment, the group will take the same teacher-made grammar test as the post-test. After that, the writer will analyze the data through paired sample t-test. The results demonstrated a significant difference between the pre-test and post-test in the student’s performance on grammar acquisition and the enhancement in learners’ motivation. Based on the findings of this research, it is believed that task-based language teaching can be used in English classes to enhance learners’ grammar achievements and motivation among Vietnamese university learners.